KEMAMPUAN BERPIKIR KRITIS SISWA SMA DALAM PEMBELAJARAN BIOLOGI - Norhasanah Norhasanah (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2018)
The teacher acts as a facilitator in improving critical thinking skills through student-centered learning. This descriptive study aims to explain the critical thinking skills of high school students in biology learning. The subjects of the study were students of SMA Negeri 4 Barabai class XI IPA 2 academic year 2016/2017 amounted to 26 people. This research was conducted February - April 2017 in SMA Negeri 4 Barabai. Types of data obtained in this study include a) Data communication ability, b) Data ability to formulate questions. Data were collected through observations and categorized by rubric 4 (excellent), 3 (good), 2 (enough) and 1 (less). The results obtained a) the ability to communicate increased (57%, 73%, 84%), b) the same is also found in the ability to formulate questions (65%, 76%, 88%).Keywords: The ability to think critically, communicate, formulate questions.